Prática de leitura e análise dos tipos de discursos em crônicas de Carlos Drummond de Andrade à luz do interacionismo sociodiscursivo - Brito, Luciana da Mota (2021)
This research proposes to dialogue about the uses of the language skills mobilized by learners through a proposal to read chronicles by Carlos Drummond de Andrade. Based on the-methodological framework of text analysis by Bronckart ([1999] 2009), the research seeks to understand how the reading and analysis of the types of discourses in the chronicles make up the corpus can contribute to the development of language skills and the language acting of the leaners, understand that the language is essential for the development of conscious and is developed through the appropriation and interiorization of the rules of action and communication. We assume the parameters based on the Sociodiscursive Interactionism theory Bronckart (1999, 2003, 2006, 2009, 2012), Cristóvão (2001) and Cristóvão and Nascimento (2005), and Machado (2004, 2007), and the methodological procedures of Didactic Engineering Dolz (2016), Dolz and Schneuwly (2004) who propose think about the process of didactic modeling and didactic transposition of text genres and the elaboration and application ofdidactic sequence. Endossed by the qualitative-interpretative approach of Saccol (2009) and Bortoni-Ricardo (2008), and the interactive reading proposal of Leurquin (2014), we develop activities that challenge the reader to think on the construction of discursive worlds and in the linguistic-discursive configuration, the types of discourses. Such studies are reconfigured in the organization of a pedagogical notebook with reading and analysis activities of chronicles by Carlos Drummond de Andrade, with aim contribute with teachers and students in the development of the language skills.